Estruvita : identificação de potenciais perigos e eventos perigosos no processo de produção, percepção e aceitabilidade de agricultores quanto ao seu uso agrícola - Bena Filho, Natanael Blanco (2019)
The chemical precipitation of struvite has received great attention in past years, due to its simplicity, speed and confiability to remove nutrients in the form of struvite cristals (MgNH4PO4.6H2O). However, the development of methods that allow the use of urine to produce agricultural fertilizer is very limited and require special care because both human and animal urines can present pathogens, trace-elements, hormones and other pharmaceuticals, which are linked with human health risk and environmental contamination. In this context, this study aimed to identify potencial hazards and hazardous events that are likely to pose health risk to users through the steps involved in the production of struvite in small scale, as well as elucidate the perception and aceptability of farmers regarding the use of estruvita from urine as fertilizer. In order to achieve that, a quali-quantitative study was performed to caracterize changes in the physico-chemical and microbiological parameters of urine during a period of 30 days. Among the results, the detectable values for E. coli and total coliforms in the female urine on the thirtieth day were highlighted.Therefore, longer storage periods (≥ 6 meses) are needed to guarantee its safe use for agriculture purposes. With respect to the presence of endocrine disrupters, different methods of analysis were performed to identify pharmaceuticals and trace-elements in different urines with higher precision. Farmacos and trace elements were analysed by High Performance Liquid Chromatography and Inductively Coupled Plasma Mass Spectrometry, respectively. The results showed that both micro-pollutants were detected in very low concentrations (µg/mL). The adapted methodologies for chemistry precipitation were shown to be promising with respect to estruvita production. This was observed with the use of Scanning Electron Microscopy and further confirmed by its purity degree that was detected using X-ray Diffraction. Therefore, it is possible to assure that substances present in struvite are not relevants to its use in agricultural activities. Based on the methodology of semi quantitative risk assessment, a method was adapted that allowed the identification of potential hazards and dangerous events in the different stages of struvite production and, after a risk analysis could help decision makers during the implementation of the process struvite production, to make its decisions based on this analysis. Also, a data collection was performed from a semi-structured mixed questionnaire applied to the farmers belonging to different agricultural production modalities of the municipality of Domingos Martins, Espírito Santo, Brazil. The Content Analysis technique, which allowed the development of analitical categories and sub-categories, was used for the determination of data. The results indicated that these farmers understand the hazards that fertilizers can impose to the environment and human health, although most of the time the risks are not perceived immediately.The acceptance of agricultural use of struvite, mainly derived from cow urine, corresponded to (36%) the preference of the farmers interviewed.